Study of electrodeposition of titanium oxide with addition of magnesium on titanium substrate with constant current - Capelin, Guilherme Ribeiro [UNESP]; Kasama Nakata, Milena Yumi [UNESP]; Uchôa Teixeira, Jean Valdir [UNESP]; Santos, Adriana Alencar [UNESP]; Lisboa Filho, Paulo Noronha [UNESP] (FapUNIFESP (SciELO), 2023)
Currently, the titanium substrate is one of the most important metallic biomaterials with application in orthopedics, dentistry, fracture fixation and knee and hip arthroplasty. Despite all these attractive properties, its biological inertia and low bactericidal capacity ends up limiting its osseointegration. In this sense, TiO2 and TiO2(MgO) coatings are performed to improve titanium characteristics, such as corrosion resistance. The objectives of this study were to analyze the corrosion resistance of titanium oxide and titanium oxide with addition of magnesium, topographies, morphologies and crystallinity on a titanium substrate through electrodeposition with constant current. Electrodepositions were performed on a three-electrode system, with titanium working electrode, Ag/AgCl as reference electrode and a platinum counter electrode in a potentiostat, and constant currents of 1.0 mA/cm2 were used for all processes. Characterizations by scanning electron microscopy (SEM), atomic force microscopy (AFM), confocal microscopy, X-Ray diffraction (XRD) and potentiodynamic polarization were used. Topography and morphology analyze indicated a change in roughness (Ra) and all demonstrated a uniform surface. The XRD analyzes indicated only metallic titanium, but all of them had a difference in the FWHM, indicating possible amorphous phases or interstitial Mg, also causing a variation in the height of the peaks. Finally, the potentiodynamic polarization indicated that the coating with TiO2 there was an improvement of 37.90% and the TiO2 with addition of magnesium there was a loss of 13.43%. Therefore, the coatings caused changes in roughness, morphologies, crystalline networks and anticorrosive properties, thus enabling the modulation of the desired properties according to the oxidation environment used.
Estudo da eletrodeposição de óxido de titânio com adição de magnésio em substrato de titânio com corrente constante